X linked exudative vitreoretinopathy: clinical features and genetic linkage analysis. Issue 3 (March 1993) - Fullwood, P; Jones, J; Bundey, S; Dudgeon, J; Fielder, A R; Kilpatrick, M W
Abstract : A four generation family in which familial exudative vitreoretinopathy is inherited as an X linked condition is described. Essentially the condition is one of abnormal vascularisation and signs at birth are those of a retinopathy superficially resembling retinopathy of prematurity, retinal folds, or, in advanced cases, enophthalmos or even phthisis. Prognosis depends on the progression of the retinal changes. The family members, including seven affected males and five obligate carrier females, have been types for 20 DNA markers, and linkage analysis suggests a gene locus either at Xq21.3 or at Xp11. As the latter region includes the locus for the gene for Norrie disease, it is possible that this and X linked vitreoretinopathy are allelic. We can further speculate that the differences in severity of the clinical manifestations are dependent only upon the timing of the insult.